Factors Affecting Speaking Performance - Desi Surlitasari Dewi; Eka Wilany (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2022)
In learning a foreign language, speaking is an essential component as it is used to deliver the meaning to interact and connect with one another. It is also often seen as an indicator of success in learning a foreign language. However, due to its interactive character, speaking in a foreign language has been identified as the most difficult ability for language learners. The study was an integrative literature review that aimed to unfold the factors that might affect speaking performance of foreign language learners. Due to the rapid pace of research, it is difficult to keep up with state-of-the-art research, so a literature review is necessary. The goal of the study is not to cover all articles ever published on the topic, but rather to combine information and ideas from different fields or past studies. In conducting the review, it will use taxonomy or classification in analyzing the reviewed studies. Approximately 20 studies including those published in research articles, book chapters, books, and other types of publications that concern the factors that may affect speaking performance are being reviewed. The finding suggests that five factors are named as determinants of speaking performance. Those are lack of L2 exposure, inhibition, anxiety, learner autonomy, motivation, and teaching pedagogy. Lack of exposure, inhibition, and anxiety were considered as negative factors of speaking performance, meanwhile a higher degree of learner autonomy and motivation as well as appropriate teaching pedagogies could be beneficial to boost FL learners’ speaking performance.